The Effects and Interconnected Roles of FinTech Crowdfunding and PropTech Innovation for Entrepreneurship in the UAE Real Estate Sector: A Stakeholder Perspective - Alyassi, Abdelrahman Mohamed Abdalla Abdelrahman; Zakaria, Norhayati (International Review of Management and Marketing, 2025)
Entrepreneurs gain financial benefits and return on investment from preordering and profit-sharing crowdfunding using technological platforms. This digital transformation significantly shapes the perspectives and approaches of entrepreneurs, particularly in their interactions with regulators, who are key stakeholders alongside financial institutions, crowdfunding platforms, and PropTech ventures. This conceptual paper uses stakeholder theory to merge PropTech and FinTech crowdsourcing to benefit stakeholders. Building an entrepreneurial behavioral model from a variety of propositions should help diverse stakeholders benefit from and understand the real estate industry’s transformation. This transition affects entrepreneurs’ attitudes and methods, including contacts with regulators, one of the important stakeholders, along with financial institutions, crowdfunding platforms, and PropTech entrepreneurship.